2013
DOI: 10.3389/fmicb.2013.00399
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of microbial diversity along a salinity gradient in the Guerrero Negro solar saltern, Baja CA Sur, Mexico

Abstract: The goal of this study was to use environmental sequencing of 16S rRNA and bop genes to compare the diversity of planktonic bacteria and archaea across ponds with increasing salinity in the Exportadora de Sal (ESSA) evaporative saltern in Guerrero Negro, Baja CA S., Mexico. We hypothesized that diverse communities of heterotrophic bacteria and archaea would be found in the ESSA ponds, but that bacterial diversity would decrease relative to archaea at the highest salinities. Archaeal 16S rRNA diversity was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
68
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 78 publications
9
68
2
Order By: Relevance
“…The equal number of genera (15 each) represented in both archaeal [10] and bacterial communities from PS differs from the observations of other authors that members of the domain Archaea are dominant, whereas those of the domain Bacteria are slightly represented in hypersaline environments [4,[21][22][23][24]. Like our study, Dillon et al [22] have reported similar archaeal and bacterial 16S rRNA diversity (four genera each) in a hypersaline pond in evaporative Guerrero Negro salterns.…”
Section: Salt Composition Of Watercontrasting
confidence: 65%
See 4 more Smart Citations
“…The equal number of genera (15 each) represented in both archaeal [10] and bacterial communities from PS differs from the observations of other authors that members of the domain Archaea are dominant, whereas those of the domain Bacteria are slightly represented in hypersaline environments [4,[21][22][23][24]. Like our study, Dillon et al [22] have reported similar archaeal and bacterial 16S rRNA diversity (four genera each) in a hypersaline pond in evaporative Guerrero Negro salterns.…”
Section: Salt Composition Of Watercontrasting
confidence: 65%
“…The unexpected high-number genera differed from the common opinion for low bacterial diversity in most of the hypersaline environments and domination of only one cluster [19,20] and determined this niche as belonging to saltern ecosystems with highest bacterial diversity. It was significantly higher than that observed by other authors in hypersaline salterns with higher than 30% salt content of the sampling site (Table 2): three bacterial genera have been established in Maras salterns, Peru [21]; five bacteral genera in a 32% salt pond, Santa Pola salterns, Spain [19]; four bacterial genera in 30% salt ponds, Guerrero Negro saltern, Mexico [22]; and five bacterial genera in the 31% salt pond S5 from a solar saltern in Tunisia [23]. The equal number of genera (15 each) represented in both archaeal [10] and bacterial communities from PS differs from the observations of other authors that members of the domain Archaea are dominant, whereas those of the domain Bacteria are slightly represented in hypersaline environments [4,[21][22][23][24].…”
Section: Salt Composition Of Watercontrasting
confidence: 58%
See 3 more Smart Citations